Non-resectable Malignant Peritoneal Mesothelioma Treated with Pressurized Intraperitoneal Aerosol Chemotherapy (PIPAC) Plus Systemic Chemotherapy Could Lead to Secondary Complete Cytoreductive Surgery: A Cohort Study - Kepenekian, Vahan; Péron, Julien; You, Benoit; Bonnefoy, Isabelle; Villeneuve, Laurent; Alyami, Mohammad; Bakrin, Naoual; Rousset, Pascal; Benzerdjeb, Nazim; Glehen, Olivier (Annals of surgical oncology, 2022)
Background Diffuse malignant peritoneal mesothelioma (DMPM) is an aggressive primary peritoneal neoplasia. At diagnosis, few patients are eligible for a recommended cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). Among neoadjuvant strategies, pressurized intraperitoneal aerosol chemotherapy (PIPAC) combined with systemic chemotherapy has been recently proposed. This study evaluated this strategy in a cohort of DMPM patients. Methods Patients with DMPM and primary or recurrent non-resectable diseases who received at least one PIPAC procedure in alternation with systemic chemotherapy were included in this retrospective study to analyze oncologic outcomes. Results Overall, 26 DMPM patients were treated with at least one PIPAC, including 20 patients with no previous CRS. Of 22 patients (85%) who had symptoms, 9 had perceptible ascites. Overall, 79 PIPAC procedures were performed, with half of the patients receiving three PIPAC procedures or more. Among eight patients (31%), 10 adverse events (13% of procedures) were reported, including two severe complications, both corresponding to digestive perforations. Improvement of symptoms was reported for 32% of the patients, whereas control of ascites was noted in 46%. All but one procedure among 14 patients (54%) secondarily treated by CRS-HIPEC were considered complete resections. After a median follow-up period of 29.6 months (95% confidence interval [CI], 17.6–not reached [NR]), the median overall survival period was 12 months (95% CI 11.1–NR). The median progression-free survival (PFS) was significantly better among the patients who underwent resection than among those who did not (33.5 vs 7.4 months; hazard ratio [HR], 0.18; 95% CI 0.06–0.755; p < 0.001). Conclusions For patients with initially non-resectable DMPM, PIPAC is feasible for treatment with neoadjuvant intent and could facilitate complete secondary resection.